Direct estimation of 17O MR images (DIESIS) for quantification of oxygen metabolism in the human brain with partial volume correction. Issue 6 (16th May 2018) - Kurzhunov, Dmitry; Borowiak, Robert; Reisert, Marco; Özen, Ali Caglar; Bock, Michael
Abstract : Purpose: To provide a data post‐processing method that corrects for partial volume effects (PVE) and fast T 2 * decay in dynamic 17 O MRI for the mapping of cerebral metabolic rates of oxygen consumption (CMRO2 ). Methods: CMRO2 is altered in neurodegenerative diseases and tumors and can be measured after 17 O gas inhalation using dynamic 17 O MRI. CMRO2 quantification is difficult because of PVE. To correct for PVE, a direct estimation of the MR images (DIESIS) method is proposed and used in 4 dynamic 17 O MRI data sets of a healthy volunteer acquired on a 3T MRI system. With DIESIS, 17 O MR signal time curves in selected regions were directly estimated based on parcellation of a coregistered 1 H MPRAGE image. Results: Profile likelihood analysis of the DIESIS method showed identifiability of CMRO2 . In white matter (WM), DIESES reduced CMRO2 from 0.97 ± 0.25 µmol/gtissue /min with Kaiser‐Bessel gridding reconstruction to 0.85 ± 0.21 µmol/gtissue /min, whereas in gray matter (GM) it increases from 1.3 ± 0.31 µmol/gtissue /min to 1.86 ± 0.36 µmol/gtissue /min; both values are closer to the literature values from the 15 O‐PET studies. Conclusion: DIESIS provided an increased separation of CMRO2 values in GM and WM brain regions and corrected for partial volume effects in 17 O‐MRI inhalation experiments. DIESIS could also be applied to more heterogeneous tissues such as glioblastomas if subregions of the tumor can be represented as additional parcels.